1986
DOI: 10.1126/science.3082009
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Gonadotropin Release by a Non-GnRH Peptide Sequence of the GnRH Precursor

Abstract: The human gonadotropin-releasing hormone (GnRH) precursor comprises the GnRH sequence followed by an extension of 59 amino acids. Basic amino acid residues in the carboxyl terminal extension may represent sites of processing to biologically active peptides. A synthetic peptide comprising the first 13 amino acids (H X Asp-Ala-Glu-Asn-Leu-Ile-Asp-Ser-Phe-Gln-Glu-Ile-Val X OH) of the 59-amino acid peptide was found to stimulate the release of gonadotropic hormones from human and baboon anterior pituitary cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Millar et al (22) found that a segment of human LHRH precursor (23) [pHLHRH- (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)] is capable of stimulating gonadotropin release from human and baboon pituitary cells. Ying et al (24) showed that the transforming growth factor type p is a potent stimulator of FSH-release in rat pituitary cells.…”
Section: Resultsmentioning
confidence: 99%
“…Millar et al (22) found that a segment of human LHRH precursor (23) [pHLHRH- (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)] is capable of stimulating gonadotropin release from human and baboon pituitary cells. Ying et al (24) showed that the transforming growth factor type p is a potent stimulator of FSH-release in rat pituitary cells.…”
Section: Resultsmentioning
confidence: 99%
“…Received: June 6, 1995 Accepted: July 26, 1995 Correspondence to: Dr. Michio TAKAHASHI, Department of Veterinary Physiology, Veterinary Medical Science, The University of Tokyo, 1-1-1 Yayoi, Bunkyo-ku, Tokyo 113, Japan a 56 amino acid peptide termed GnRH-associated peptide (GAP) by processing [3].…”
Section: Gonadotropin-releasingmentioning
confidence: 99%
“…Kopple et al [14] found that NMR data on LHRH antagonists did not indicate a preferred conformation. Millar et al [15] studied gonadotropin release by a non-GnRH sequence of the GnRH precursor. Sundaram et al [16] observed species differences in the effects of an antagonist.…”
Section: Introductionmentioning
confidence: 99%